Pembelajaran IPS Untuk Melatih Sikap Sosial Anak SD/MI - Marifatul Ilmi; Alisa Alistiana; Ainur Risalah; Devi Sakinatus Shofiyah; Laelatul Azizah (JIEES : Journal of Islamic Education at Elementary School, 2022)
This article aims to find out how students' social attitudes are through social studies learning and to train students' discipline through social studies learning as well as a means for students to instill social attitudes. This article uses the literature review method by tracing various critical reference sources to get the correct data. The results of this article indicate that social attitudes can be formed in social studies learning with the direction of the teacher providing examples of doing good social attitudes and the means for socially training students can be done with outside activities. In this way, students can train their social attitudes from an early age, if social behavior is abandoned it will be carried over to adulthood to carry out deviant social attitudes. Therefore, social attitudes must be formed and applied from an early age so that they can understand which attitudes can be imitated and which cannot be imitated. Through social studies learning, it is expected that students can take the values of social attitudes that exist in learning. The role of the teacher is also very much needed in providing good examples of attitudes and social interactions that must be applied in social life. The results of the application of social attitudes can be seen by the teacher when interacting with students, from there the teacher can conclude how well they are in applying the social attitudes that have been instilled by the teacher through social studies learning.